¿Son las cosas tan simples y claras como parecen? Dificultad en la categorización de schwas y consonantes silábicas inglesas - Arboleda Guirao, Inmaculada de Jesús (Huarte de San Juan. Filología y Didáctica de la Lengua, 2012)
This paper reports a study based on Arboleda (2010) which goes deeper into the perceptual behaviour of English syllabic consonants in emphatic or phrase final position. The findings in Arboleda (2010) make us wonder whether clarity in production has an influence in the degree of disagreement amongst the judges at the time of identifying a schwa or a syllabic consonant in certain words. The studies devoted to going deeper into the use and perception of syllabic consonants have been limited (Monroy, 1980; van Bergem, 1995). The data in Arboleda (2010) were complemented with an acoustic analysis of a sample of sounds and a post-task questionnaire. The results show that the clarity in production results to be determining. Despite the solidity of the findings, in a more exhaustive study it would be advisable to explore this phoneme further, which is neither schwa nor syllabic consonant and is the cause of the disagreement amongst the listeners in Arboleda (2010).